2006
DOI: 10.1159/000093711
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic Inflammation, Remodeling of Lower Airway, Bronchial Responsiveness and Cough Reflex Sensitivity in Non-Asthmatic Subjects with Nasal Allergy

Abstract: Background: It has been reported that nasal allergy influences the lower airway inflammation and functions. We elucidated whether nasal allergy would contribute to lower airway inflammation and functions. Methods: 266 subjects aged 21–39 years were interviewed with special emphasis on history of asthma and nasal allergies (perennial allergic rhinitis (PAR) and seasonal allergic rhinitis (Japanese cedar pollinosis; PO)). Symptomatic subject was defined when nasal symptoms were present during a 3-week study peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
6
0
1
Order By: Relevance
“…It has been reported that allergic rhinitis can cause asymptomatic lower airway eosinophilic inflammation and BHR . This eosinophilic inflammation was decreased with the avoidance of allergens, and BHR was reversible after corticosteroids treatment .…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that allergic rhinitis can cause asymptomatic lower airway eosinophilic inflammation and BHR . This eosinophilic inflammation was decreased with the avoidance of allergens, and BHR was reversible after corticosteroids treatment .…”
Section: Discussionmentioning
confidence: 98%
“…Eosinophilia in the lower airway is common in patients with allergic rhinitis who only presented with nasal symptoms, as evaluated by bronchoalveolar lavage fluids, bronchial mucosa biopsies, and induced sputum [25,26]. Furthermore, sinusitis is usually characterized by chronic upper and lower airway inflammation [27].…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated by Bardin et al [9], aspiration of nasolaryngeal secretions into the lung could not explain the occurrence of cough in the patients with UACS, even though the possibility could not completely excluded in our study. We believe the lower airway inflammation in the patients with UACS may represent the airway manifestation of systematic allergic reaction in the case of allergic rhinitis [26,33] or the extension of upper airway inflammation by unknown mechanisms as observed in sinusitis [34]. …”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation could be that, whereas nasal lavage fluid levels represent the local inflammatory ‘burden’, serum levels reflect the systemic nature of inflammation, including the presence of subclinical inflammation in bronchial mucosa. Several studies have demonstrated an increased bronchial hyper‐responsiveness in non‐asthmatic patients with allergic rhinitis as well as a correlation between the level of hyper‐responsiveness and sputum eosinophils (13–15). Activated eosinophils in bronchial tissue have been observed in patients with clinical asthma as well as in atopic non‐asthmatics, demonstrating the presence of subclinical mucosal inflammation (16), and it would seem natural to expect this in future patients with symptomatic asthma.…”
Section: Discussionmentioning
confidence: 99%